Aristolochic acid-associated cancers: a public health risk in need of global action - Das, Samrat; Thakur, Shefali; Korenjak, Michael; Sidorenko, Viktoriya S; Chung, Felicia Fei Lei *; Zavadil, Jiri (Nature Research, 2022)
Aristolochic acids (AAs) are a group of naturally occurring compounds present in many plant species of the Aristolochiaceae family. Exposure to AA is a significant risk factor for severe nephropathy, and urological and hepatobiliary cancers (among others) that are often recurrent and characterized by the prominent mutational fingerprint of AA. However, herbal medicinal products that contain AA continue to be manufactured and marketed worldwide with inadequate regulation, and possible environmental exposure routes receive little attention. As the trade of food and dietary supplements becomes increasingly globalized, we propose that further inaction on curtailing AA exposure will have far-reaching negative effects on the disease trends of AA-associated cancers. Our Review aims to systematically present the historical and current evidence for the mutagenicity and carcinogenicity of AA, and the effect of removing sources of AA exposure on cancer incidence trends. We discuss the persisting challenges of assessing the scale of AA-related carcinogenicity, and the obstacles that must be overcome in curbing AA exposure and preventing associated cancers. Overall, this Review aims to strengthen the case for the implementation of prevention measures against AA's multifaceted, detrimental and potentially fully preventable effects on human cancer development.